Effect of residence time on the morphology of silica nanoparticles synthesized in a microfluidic reactor - Fiona Ling, Wang Ming; Abdulbari, Hayder A.; Chin, S. Y. (Springer, 2021)
In the present work, silica nanoparticles were synthesized, adapting the conventional sol-gel method in both bench and microflow systems for comparison purposes. A custom-made polydimethylsiloxane microreactor, consisting of a T-junction as droplet generator, was first designed and fabricated using the direct writing lithography method. The process involved tetraethyl orthosilicate as a precursor, acetic acid as a catalyst, and water as a hydrolyzing agent. The produced silica nanoparticles were characterized using transmission electron microscopy (TEM), Energy-dispersive X-ray (EDX), and X-ray diffraction (XRD) analysis. The silica nanoparticles produced from the bench-scaled sol-gel method showed poor monodispersity with irregular configuration and a mean particle size of 95 ± 4 nm. Meanwhile, the microflow system’s silica nanoparticles showed high monodispersity, perfectly spherical shapes, and a narrower particle size distribution with an average of 5.76 ± 1.27 nm. A reduction of particle size by about 93.94% was achieved using a microflow system. The effect of residence time on the size of silica nanoparticles was conducted by varying the operating pressure that affect the flow rate. Reducing the residence time from 95.65 s to 38.72 s reduces the size from 5.76 nm to 4.89 nm. The shorter residence time also reduces the size distribution to 1.11 nm. However, aggregation of silica nanoparticles was observed, indicating particle growth stage took place. Increasing the aging time for silica nanoparticle synthesis showed a negative effect where large silica up to 1 μm was produced hence lowering the dispersity. EDX and XRD analysis confirmed that silica nanoparticles with high purity were obtained from a droplet-based microreactor.